Digital radiography as an alternative method in the evaluation of bone density in uremic rats - Castro,Bárbara Bruna Abreu de (2020)
ABSTRACT Introduction: Digital radiography (DRx) may provide a suitable alternative to investigate mineral and bone disorder (MBD) and loss of bone density (BD) in rodent models of chronic kidney disease (CKD). The objective of this study was to use DRx to evaluate BD in CKD rats, and to evaluate the correlation between DRx findings and serum MBD markers and bone histomorphometry. Methods: Uremia was induced by feeding Wistar rats an adenine-enriched diet (0.75% for 4 weeks/0.10% for 3 weeks); outcomes were compared to a control group at experimental weeks 3, 4, and 7. The following biochemical markers were measured: creatinine clearance (CrC), phosphate (P), calcium (Ca), fractional excretion of P (FeP), alkaline phosphatase (ALP), fibroblast growth factor-23 (FGF-23), and parathyroid hormone (PTH). DRx imaging was performed and histomorphometry analysis was conducted using the left femur. Results: As expected, at week 7, uremic rats presented with reduced CrC and higher levels of P, FeP, and ALP compared to controls. DRx confirmed the lower BD in uremic animals (0.57±0.07 vs. 0.68 ± 0.06 a.u.; p = 0.016) compared to controls at the end of week 7, when MBD was more prominent. A severe form of high-turnover bone disease accompanied these biochemical changes. BD measured on DRx correlated to P (r=-0.81; p = 0.002), ALP (r = -0.69, p = 0.01), PTH (r = -0.83, p = 0.01), OS/BS (r = -0.70; p = 0.02), and ObS/BS (r = -0.70; p = 0.02). Conclusion: BD quantified by DRx was associated with the typical complications of MBD in CKD and showed to be viable in the evaluation of bone alterations in CKD.